2-Dimensional homogenization FEM analysis of hyperelastic foamed rubber - Nomoto, A.; Yasutaka, H.; Oketani, S.; Matsuda, A. (Procedia Engineering, 2016)
Foamed rubbers are widely used for the shoe-soles, shin-guards, protectors and so on. The complex microstructure of foamed rubber consists of rubber matrix and pores. Therefore, foamed rubbers show good shock-absorbing properties in addition to good formability and lightweight. The mechanical characteristics of foamed rubber are determined by the mechanical characteristics of rubber matrix and its microstructure.